Level of Disclosure of Corporate Social Responsibility Information in Lithuanian Companies Trading on the Nasdaq Baltic Stock Exchange - Jefimova, Emilija Alenksandra; Kalniūtė, Deimantė; Bachtijeva, Diana (Buhalterinės apskaitos teorija ir praktika, 2023)
In today's market conditions and in the context of sustainable business, the provision of social responsibility information to information consumers is important. This paper focuses on corporate social responsibility disclosure and its importance in communicating with stakeholders. It examines the problem of information asymmetry faced by companies and the possibility of signalling to the most powerful stakeholder groups about their involvement in social activities. The paper develops a model for the calculation of a corporate social responsibility disclosure index. Based on the developed model, an empirical study was carried out to calculate the social responsibility disclosure index of companies listed on the Nasdaq Baltic Stock Exchange. The study found that over the period 2017-2022, the total amount of disclosures increased by 14.85%. It also assessed the amount and dynamics of disclosures in individual areas (environmental, social and HR-related, human rights, corruption and bribery, and verification of the implementation of corporate processes). The CSR disclosure model developed is universal and can be used to calculate a CSR disclosure index for all non-financial companies.
Keywords: corporate social responsibility; corporate social responsibility disclosure; signal theory; stakeholder theory